Zaharia Bârsan and The Establishment of the National Theatre in Cluj - CEUCA, Justin (Studia Universitatis Babeș-Bolyai Dramatica, 2018)
The article tackles the circumstances in which the National Theatre in Cluj came into being and its relevance to the Romanian cultural scene. It was inaugurated on the 1st of December 1919 after the Unification of Transylvania and Romania on the 1st of December 1918. To have professional theatre performed in the mother tongue of the majority was the embodiment of an age-old yearning of the Romanians living in this region, and was supported by the entirety of the theatre movement. In this respect, the most important aspects are mentioned. Before the Unification, Transylvania was part of the Austro-Hungarian Empire, and Romanians, despite forming the largest segment of the population, were completely stripped of rights. Therefore, the new-born National Theatre in Cluj was invested with a plurality of missions, the main one being to stand as an expression and a stimulus of Romanian creativity in all Transylvania, which was materialized through tours and series of performances in the region. The paper also attempts to capture the complexity of Zaharia Bârsan’s personality, a reputable theatrical animator, actor, director, teacher, dramatist, poet, prose writer, who was the first to be invested as director and founder of the institution. The difficulties he had to overcome, which revolved around founding a troupe of talented actors, finding a repertoire and bestowing the theatre with an aura of prestige are analysed. Initially, the repertoire included classical pieces, which were thought to carry a clearer, more accessible message, but he introduced modern and Romanian pieces as well. Zaharia Bârsan managed to produce extraordinary performances right from the first theatrical seasons: Vlaicu Vodă by Al. Davila, Oedipus Rex by Sophocles, Shakespeare’s Hamlet and Macbeth.